THE CITTASLOW CERTIFICATION AND ITS EFFECTS ON SUSTAINABLE TOURISM GOVERNANCE - Presenza, Angelo; Abbate, Tindara; Perano, Mirko (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2015)
The paper examines the relationship between sustainable tourism governance and Cittaslow certification. As an organised network of small cities, Cittaslow is attempting to focus plans around the primary assets of locality-based identity, by choosing to preserve the unique characteristics of each urban area. Through a quantitative analysis, based on International Cittaslow certified cities, the paper aims to examine the effects of Cittaslow certification on local government for the implementation of more sustainable tourism governance. Findings reveal that interest in being certified acts as a stimulus to the definition and the implementation of more sustainable development, allowing a destination to become part of an international network of cities. The results highlight the need to fully exploit the various opportunities in order to be certified, moving primarily from the implementation of policy initiatives coherent not only with the many requirements laid down by Cittaslow, but which have a positive impact on areas considered more strategic for small town development, while avoiding the waste of effort and scarce resources on other less focused projects.